Children‘s beliefs about parental divorce - Dovydaitienė, Miglė (Psichologija, 2001)
This article investigates children’s beliefs about parental divorce and attitudes toward environment and people. Children’s believes about parental divorce is evaluated in a sample 8 through 10-year children whose parents had been separated for about 3 years. Attitudes toward environment and people between children of separated as well as intact families is compared. We also examined the relation of children’s beliefs about parental divorce and attitudes toward environment and people. The mediating effect of gender stresses in divorced and intact families and time since divorce is discussed. The analyses of results revealed that hope of reunification and parental blame occur most frequently. Chil-dren also are afraid of abandonment and common beliefs are peer ridicule and avoidance. Beliefs of Lithua-nian and American samples is being compared. The results in general are consistent with data of other investigators of the subject. We make a point on the relation of children’s beliefs about parental divorce and attitudes toward environment and other people and stress the importance of children’s attitude and beliefs toward children’s vulnerability. Possible conclusion is that child-ren’s attitude toward environment is effected by divorce experiences, and primary cognitive - social factors, such as divorce understanding, beliefs about divorce.